Padrão de sexualidade ineficaz de idosos com Diabetes mellitus. - Cristina Severina, Isabella; Ramos de Lima, Luciano; Schwerz Funghetto, Silvana; Silva Santos, Walterlânia; Grou Volpe, Cris Renata; Morato Stival, Marina (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2022)
Objective: to investigate the nursing diagnosis ineffective sexuality pattern in elderly people with Diabetes mellitus in primary care and analyze their sexuality profile. Method: this is a cross-sectional study carried out in a Basic Health Unit with a sample of 134 elderly diabetics. Interviews were carried out between July and August 2019 with structured instruments and laboratory tests. An instrument was used to investigate the nursing diagnosis ineffective sexuality pattern with conceptual and operational definitions of the defining characteristics and related factors according to the NANDA-I taxonomy (2018-2020). Results: women predominated, although men were more sexually active (p < 0.001). Younger people were more sexually active (p = 0.001). Regarding hormonal parameters, elderly people with higher testosterone levels reported being sexually active (p < 0.001). Most do not use condoms during sexual intercourse. When analyzing the nursing diagnosis of ineffective sexuality pattern, the most prevalent defining characteristic was “a change in sexual behavior” and the related factor was “skills deficit in sexuality-related alternatives”. Conclusions and implications for practice: the nursing diagnosis ineffective sexuality pattern has importance in assessing elderly diabetics, as sexuality influences their behavior and personal satisfaction.